Characteristics, management, and blood pressure control in patients with apparent resistant hypertension in the US. Issue 2 (February 2023) - Ammann, Eric M.; O'Brien, Ellen S.; Milentijevic, Dejan; Kharat, Akshay A.; Talbot, Darren A.; Canovatchel, William; Haskell, Lloyd; Andrawis, Nabil S.
Abstract: Background: Per treatment guidelines, resistant hypertension is defined as uncontrolled blood pressure (BP) while taking 3 concomitant antihypertensives (AHTs) or controlled BP while taking ≥4 AHTs. Characteristics, AHT therapy use, and BP control were analyzed in US patients with hypertension who were prescribed ≥3 classes of AHT medications. Methods: This retrospective analysis of the Optum® Electronic Health Record Database evaluated patients ≥18 years of age with a diagnosis of hypertension classified based on the number of prescribed AHT medication classes (3, 4, or ≥5). For the primary analysis, uncontrolled hypertension was defined as systolic BP (SBP) ≥140 mmHg or diastolic BP (DBP) ≥90 mmHg. For secondary analyses, uncontrolled hypertension was defined as SBP ≥130 mmHg or DBP ≥80 mmHg. Results: 207, 705 patients with hypertension and concurrent use of ≥3 AHT medication classes were included. Diuretics, beta blockers, ACE inhibitors and/or ARBs, and CCBs were the most prescribed classes; thiazides and thiazide-like agents were the most prescribed diuretics. Among patients who were prescribed 3, 4, or ≥5 AHT medication classes, approximately 70% achieved a BP goal of <140/90 mmHg; approximately 40% achieved BP <130/80 mmHg. After ≥1 year of follow-up, the number of concurrent AHT medication classes was unchanged from baseline in the majority of patients and the prevalence of uncontrolled hypertension (≥140/90 mmHg) was similar. Conclusions: This study illustrates suboptimal BP control in many patients with apparent resistant hypertension despite the use of multidrug regimens and suggests a need for new drug classes and regimens that effectively manage resistant hypertension.